2022
DOI: 10.14742/ajet.7081
|View full text |Cite
|
Sign up to set email alerts
|

Smart classroom preferences and information literacy among college students

Abstract: In recent years, smart classrooms have been widely constructed in colleges and universities. To help the design of student-centred smart classroom in compliance with students’ information literacy levels and enable all students to adapt to the smart classroom smoothly, this study utilised a quantitative method to investigate the information literacy and preferences for smart classroom learning environments (PSCLE) of 873 Chinese college students. The results indicated statistically significant effects of colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…Therefore, students would have better perceptions of the smart classroom, interact more in the smart classroom, and ultimately, achieve better performance in the smart classroom in contrast to the “quasi smart” classroom ( Xu et al, 2018 ). Although Yu et al (2022) reported no significant difference in either the interpersonal interaction or the human–technology interaction between the smart and “quasi smart” classroom environments, students were significantly more engaged in the smart classroom than in the “quasi smart” classroom.…”
Section: Literature Reviewmentioning
confidence: 86%
See 2 more Smart Citations
“…Therefore, students would have better perceptions of the smart classroom, interact more in the smart classroom, and ultimately, achieve better performance in the smart classroom in contrast to the “quasi smart” classroom ( Xu et al, 2018 ). Although Yu et al (2022) reported no significant difference in either the interpersonal interaction or the human–technology interaction between the smart and “quasi smart” classroom environments, students were significantly more engaged in the smart classroom than in the “quasi smart” classroom.…”
Section: Literature Reviewmentioning
confidence: 86%
“…Previous study showed that the effective interaction such as the interpersonal interaction between the instructor and students, peer to peer interaction, human-tech interaction supporting instructor's presentation and management were enhanced in the smart classroom, and the classroom atmosphere 10.3389/fpsyg.2022.1047027 was also more harmonious (Yu et al, 2022). Intelligent devices provide more opportunities for the instructor to provide timely and effective guidance to students, and promote individualized and differentiated communication between students and the instructor in the smart classroom.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the literature review, the research on the perceived learning efficiency of Chinese college students in smart classroom environment has received more attention (Hu et al. , 2022; Yu et al. , 2022b).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Information literacy is the ability to locate, access, assess and use information from variety sources, and represents a key dimension of digital and media literacy [10]. Information literacy is more than the ability to find and present information, but about high-level analysis, synthesis, critical thinking, and problem solving [11]. Therefore, information literacy may be perceived and experienced in a variety of ways.…”
Section: Introductionmentioning
confidence: 99%